1994
DOI: 10.1177/155005949402500106
|View full text |Cite
|
Sign up to set email alerts
|

P300 Event-Related Potentials in Epileptic Children

Abstract: To evaluate the cognitive function of epileptic children, we examined P300 in 50 patients, 32 with idiopathic generalized epilepsy (IGE) and 18 with temporal lobe epilepsy (TLE), and 39 normal children. There were significant negative correlations between age and P300 latencies at Pz and Cz in normal controls. For data analysis, we used the age-corrected latency, which was calculated as the interval between the actual and predicted P300 latencies. The predicted latency was calculated with the regression equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
0
23
1
Order By: Relevance
“…Sun et al 27 found that epilepsy duration was associated with delayed P300 latency. These findings were not confirmed in another studies 10,30 . It is known that P300 latency can increase when there is difficulty in the oddball paradigm 15 .…”
Section: Side Groupscontrasting
confidence: 63%
“…Sun et al 27 found that epilepsy duration was associated with delayed P300 latency. These findings were not confirmed in another studies 10,30 . It is known that P300 latency can increase when there is difficulty in the oddball paradigm 15 .…”
Section: Side Groupscontrasting
confidence: 63%
“…Event-related potential (ERP) is an important method to evaluate the cognitive status of epilepsy patients (e.g., Sunaga et al, 1994;Soysal et al, 1999;Rodin et al, 1999;Tendon and Duban, 2000;Trinka et al, 2000;Sun et al, 2007). Differences in timing and scalp topography of particular ERP components allow inferences about the timing and spatial characteristics of brain activity involved in cognitive processing (Rugg and Coles, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Sunaga showed significant differences in P300 latency with IGE, but not with TLE [3]. He speculated that dysfunction of the mesencephalic reticular formation and thalamus may contribute to prolongation of P300 in children with IGE [3]. On the other hand, Shimono [9], Chayasirisobhon [18] and Bocquillon [22] showed no significant difference in P300 latency with SPE or TLE.…”
Section: P300: the Clinical Aspects Of Epilepsymentioning
confidence: 82%
“…Furthermore, patients with temporal lobe epilepsy (TLE) displayed prolonged P300 latencies compared to patients with IGE [2,12]. In contrast, Sunaga showed significant differences in P300 latency with IGE, but not with TLE [3]. He speculated that dysfunction of the mesencephalic reticular formation and thalamus may contribute to prolongation of P300 in children with IGE [3].…”
Section: P300: the Clinical Aspects Of Epilepsymentioning
confidence: 94%